2011
DOI: 10.1002/jpln.201000390
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined application of vermicompost and mineral fertilizer on the growth of Allium cepa L. and soil fertility

Abstract: The promotion of organic farming involves curtailing extensive use of mineral fertilizers. The present study was aimed to compare the effects of vermicompost (10 Mg ha -1 ), commercial mineral fertilizer (NPK-100:80:80), and their combination on (1) the growth of a major cash crop "onion" (Allium cepa L.) and (2) the changes that may have occurred in the amended soil. The experiment was a randomized complete block design with four replications during the crop-growing season of 2008/09. Results showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 36 publications
5
34
0
1
Order By: Relevance
“…Mixed fertilizer treatments resulted in higher stem diameter than the other treatments, which are consistent with the study of Srivastava et al (2012). They reported that the combination of chemical fertilizer with organic materials significantly increased the number of leaves, diameter, fresh weight and leaf length.…”
Section: Growth Performance Of Kenafsupporting
confidence: 86%
See 1 more Smart Citation
“…Mixed fertilizer treatments resulted in higher stem diameter than the other treatments, which are consistent with the study of Srivastava et al (2012). They reported that the combination of chemical fertilizer with organic materials significantly increased the number of leaves, diameter, fresh weight and leaf length.…”
Section: Growth Performance Of Kenafsupporting
confidence: 86%
“…Growth parameter of different kenaf parts and soil parameters were analyzed using Analyses of Variance (ANOVA), followed by Duncan's Multiple Range Test Test (DMRT) to detect the significant difference among the treatments (SAS, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The superiority of the treatment may be due to the fact that it might have taken advantage of the merits conferred by both vermicompost and chemical fertilizer in a most poised condition. As suggested by Srivastava et al (2012), the integrated application of vermicompost and mineral fertilizer in appropriate ratio resulted in more balanced nutrient contents, microbial population and OM. This might have led to increased uptake of essential nutrients which in turn resulted in increased vegetative growth of the plant to help for better carbohydrate build up that subsequently contributed to higher fruit yield and quality components (Suge et al 2011).…”
Section: Effect Of Different Doses Of Vermicompost and Np Fertilizersmentioning
confidence: 92%
“…Karaka and Bhattacharyyab (2011) as nitrogen fertilizer due to its high nitrogen content, which is the limiting nutrient for plant growth (Srivastava et al, 2012). Furthermore, Heinonen-Tanski et al (2007) report that urine can replace commercial fertilizer, and can be used in soils with low nitrogen availability.…”
Section: Foliar Analysismentioning
confidence: 99%
“…Karaka y Bhattacharyyab (2011) reportaron que la orina puede ser utilizada como fertilizante nitrogenado debido a su alto contenido de nitrógeno, el cual es el nutriente limitante para el crecimiento de las plantas (Srivastava et al, 2012). Además, Heinonen-Tanski et al (2007) reportan que la orina puede reemplazar a los fertilizantes comerciales, y que puede ser utilizada en suelos con baja disponibilidad de nitrógeno…”
Section: Análisis Foliarunclassified